1979
DOI: 10.1152/jn.1979.42.5.1370
|View full text |Cite
|
Sign up to set email alerts
|

Responses of primate spinothalamic neurons to graded and to repeated noxious heat stimuli

Abstract: 1. The responses of primate spinothalamic tract cells innervating the glabrous skin of the foot to noxious thermal stimuli have been examined. 2. Of the 41 cells studied, 98% responded to noxious thermal stimuli. Heating the cutaneous receptive field with a series of stimuli from 35 to 43, 47, and 50 degrees C produced a graded increase in discharge rate. The responses were characterized by an onset, which occurred after the temperature change had either slowed or stopped, an acceleration in the discharge up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
42
2
1

Year Published

1979
1979
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(59 citation statements)
references
References 0 publications
13
42
2
1
Order By: Relevance
“…Indeed the main properties of lamina I neurons are close to those of PoT nociceptive neurons: (1) numerous lamina I neurons respond strongly and specifically to noxious stimuli (Christensen and Perl, 1970;Bester et al, 2000), and (2) the slope of the stimulus-response curve of lamina I neurons is maximum between 46 and 50°C (Kenshalo et al, 1979;Bester et al, 2000). However, the receptive fields of lamina I neurons were generally small or very small (typically one digit) (Kenshalo et al, 1979;Bester et al, 2000), whereas those of PoT neurons were markedly larger (one to three portions of the body). This last point likely reflects a strong convergence of lamina I projections within the PoT (Gauriau and Bernard, 2004).…”
Section: Ns Neuronsmentioning
confidence: 79%
See 1 more Smart Citation
“…Indeed the main properties of lamina I neurons are close to those of PoT nociceptive neurons: (1) numerous lamina I neurons respond strongly and specifically to noxious stimuli (Christensen and Perl, 1970;Bester et al, 2000), and (2) the slope of the stimulus-response curve of lamina I neurons is maximum between 46 and 50°C (Kenshalo et al, 1979;Bester et al, 2000). However, the receptive fields of lamina I neurons were generally small or very small (typically one digit) (Kenshalo et al, 1979;Bester et al, 2000), whereas those of PoT neurons were markedly larger (one to three portions of the body). This last point likely reflects a strong convergence of lamina I projections within the PoT (Gauriau and Bernard, 2004).…”
Section: Ns Neuronsmentioning
confidence: 79%
“…Because lamina I neurons are involved primarily in nociceptive processing (Christensen and Perl, 1970;Kenshalo et al, 1979;Bushnell et al, 1984;Craig and Kniffki, 1985;Bester et al, 2000), it is probable that they provide the main nociceptive input to PoT NS neurons. Indeed the main properties of lamina I neurons are close to those of PoT nociceptive neurons: (1) numerous lamina I neurons respond strongly and specifically to noxious stimuli (Christensen and Perl, 1970;Bester et al, 2000), and (2) the slope of the stimulus-response curve of lamina I neurons is maximum between 46 and 50°C (Kenshalo et al, 1979;Bester et al, 2000). However, the receptive fields of lamina I neurons were generally small or very small (typically one digit) (Kenshalo et al, 1979;Bester et al, 2000), whereas those of PoT neurons were markedly larger (one to three portions of the body).…”
Section: Ns Neuronsmentioning
confidence: 99%
“…Studies suggest, for example, that intense noxious stimulation or tissue injury can produce dramatic changes in sensitivity to both noxious and non-noxious stimulation as well as expansion of the receptive fields of neurons of the dorsal horn (Perl et al, 1976;Price et al, 1978;Kenshalo et al, 1979Kenshalo et al, , 1982McMahon and Wall, 1984;Woolf and King, 1990;Simone et al, 1991;Dougherty and Willis, 1992;Coderre et al, 1993). Sensitization and expansion of receptive fields in response to inflammation and tissue injury or electrical nerve stimulation have also been demonstrated in the thalamus (Guilbaud et al, 1986) and somatosensory cortex (Lamour et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Dorsal horn neurons fire with increasing frequency in response to repeated applications of a noxious heat stimulus (Perl 1976;Kenshalo et al 1979). This sensitization of dorsal horn neurons occurs after various types of tissue injury including thermal injury (Price et al 1978;Kenshalo et a1.…”
Section: Central Sensitizationmentioning
confidence: 99%
“…Only recently has there been specific empirical evidence indicating noxious stimulus-induced changes in CNS function. The studies of Perl (1976) and Kenshalo et al (1979) were the first to demonstrate that noxious peripheral stimuli do produce changes in the sensitivity of dorsal horn neurons to further stimulation; while Woolf and Wall (Woolf 1983;Woolf and Wall 1986a) were the first to provide empirical evidence for a primary afferent input triggering sustained increases in central excitability. Woolf (1983) demonstrated that injury-induced increases in spinal cord excitability could be maintained even after local anesthesia of the injured site, providing empirical evidence that acute injury could produce lasting spinal changes.…”
Section: Pain and Neuroplasticity: A Developing Theorymentioning
confidence: 99%